Strategies For Forming Actions to Determine The Next Speaker in Informal Conversations: a Comparative Study in Javanese And Japanese - Nirbito Hanggoro Pribadi; Kenfitria Diah Wijayanti; Astiana Ajeng Rahadini; Favorita Kurwidaria; Dewi Pangestu Said; Prima Veronika; Eni Sri Budi Lestari (Program Studi Pendidikan Bahasa dan Sastra Indonesia, Fakultas Ilmu Pendidikan, Universitas Timor, 2025)
This study explores techniques for determining the next speaker in informal conversations involving Javanese and Japanese-speaking adolescents. The focus of the study is on the techniques used by these speakers to determine the next speaker. The dataset was obtained through observation of informal conversations between Javanese and Japanese-speaking adolescents. The collected data was then analysed using conversation analysis by looking at the practice of using strategies to determine the next speaker, both verbal and non-verbal. The results show that name greetings and eye contact gestures are used as effective techniques to deal with the issue of orientation regarding who will be the next speaker. These findings offer a dimension for describing similarities and specific techniques in the diversity and commonalities of cross-linguistic and cross-cultural conversations.